Global Religions and International Relations: A Diplomatic Perspective - Pasquale Ferrara (Palgrave Macmillan, 2013)
The study of religion in the context of international relations is experiencing a resurgence in attention and scholarship, serving as a crucial method of understanding world events through the cultural prism of faith. Religion's ability to confer legitimacy, influence world opinion of leaders and figureheads, and the tendency for religious conflicts to spill over borders all constitute ways in which faith shapes international relations. However, as this book demonstrates, the role of religion is also increasingly important in promoting forms of organized and institutionalized international cooperation, especially in terms of cooperative activity between states and non-state international actors. As global power shifts, a discussion of the role religions play within systemic analysis of international relations and diplomacy is vital toward understanding the future of religion in an increasingly globalized world.